Hylomecon japonica var. dentipetala (Papaveraceae), a new variety from western Hubei, China - Du, Wei; Li, Ya; Tan, Fei (Phytotaxa, 2019)
Hylomecon japonica var. dentipetala, a new variety of the Papaveraceae from western Hubei in central China, is described and illustrated. The new variety differs from its type variety, var. japonica, by its irregularly dentate or erose petals.